Luminescent Down‐Conversion Semiconductor Quantum Dots and Aligned Quantum Rods for Liquid Crystal Displays. Issue 22 (11th October 2019) - Srivastava, Abhishek K.; Zhang, Wanlong; Schneider, Julian; Halpert, Jonathan E.; Rogach, Andrey L.
Abstract: Herein, emerging applications of luminescent semiconductor nanocrystals are addressed, such as quantum dots and quantum rods as down‐conversion materials used in liquid crystal displays (LCD). Their precisely tunable emission wavelengths and narrow emission bandwidths offer high color purity resulting in a wide color gamut with vivid colors for LCDs. Anisotropic materials, such as quantum rods, have the additional advantage of polarized emission, which can bring a significant improvement to the efficiency of LCD displays. The basic optical properties of these nanomaterials are considered, with a focus on quantum rods, and the challenges and progress in their assembly are discussed. Different techniques for quantum rod alignment are introduced such as shear‐oriented, electric field and magnetic field assisted assembly, mechanical rubbing, stretching, and electrospinning. The photoalignment approach allows for an easy arrangement of quantum rods in‐plane, and the implications of this method to patterning are considered. Different configurations of LCDs utilizing semiconductor quantum dots and quantum rods as down‐conversion layers are also presented, and the potential applications that are enabled by the wide range of emerging materials are highlighted. Abstract : Herein, emerging applications of luminescent semiconductor nanocrystals are addressed with a focus on anisotropic quantum rods as down‐conversion materials for liquid crystal displays (LCDs). Techniques for the quantum rod alignment, with a focus on the photoalignment approach, and different configurations of LCDs are considered.